Latin America in the context of Chinese economic growth: the problem of the super elasticity of imports - Paikin, Damián; Albornoz, Maximiliano (Latin American Journal of Trade Policy, 2023)
The China’s demand for primary products reopened a debate in Latin America on the valuation of this trade relationship. On the one hand, some analysts see it as a great opportunity to place Latin American products. On the other hand, others have remarked the deindustrialization of exports and the growing the commodities in the basket. In this context, the work intends to contribute a further element to the debate, based on a quantitative analysis through the estimation of the bilateral elasticities of trade between China and three countries of the region, Argentina, Brazil, and Uruguay for the period 1997-2019. This view allows us to understand to what extent this trade favors (or not) the growth of the countries based on an analysis of the impact of the partner’s import basket in the face of an increase in national income.